Crystal structure of the magnetobacterial protein MtxA C-terminal domain reveals a new sequence-structure relationship - Davidov, Geula; Müller, Frank D.; Baumgartner, Jens; Bitton, Ronit; Faivre, Damien; Schüler, Dirk; Zarivach, Raz (Frontiers in Molecular Biosciences, 2015)
Magnetotactic bacteria (MTB) are a diverse group of aquatic bacteria that have the magnetotaxis ability to align themselves along the geomagnetic field lines and to navigate to a microoxic zone at the bottom of chemically stratified natural water. This special navigation is the result of a unique linear assembly of a specialized organelle, the magnetosome, which contains a biomineralized magnetic nanocrystal enveloped by a cytoplasmic membrane. The Magnetospirillum gryphiswaldense MtxA protein (MGR_0208) was suggested to play a role in bacterial magnetotaxis due to its gene location in an operon together with putative signal transduction genes. Since no homology is found for MtxA, and to better understand the role and function of MtxA in MTB’s magnetotaxis, we initiated structural and functional studies of MtxA via X-ray crystallography and deletion mutagenesis. Here, we present the crystal structure of the MtxA C-terminal domain and provide new insights into its sequence-structure relationship.